Flexible Fibers: Polymer Fiber Probes Enable Optical Control of Spinal Cord and Muscle Function In Vivo (Adv. Funct. Mater. 42/2014). (7th November 2014) - Lu, Chi; Froriep, Ulrich P.; Koppes, Ryan A.; Canales, Andres; Caggiano, Vittorio; Selvidge, Jennifer; Bizzi, Emilio; Anikeeva, Polina
<x xml:space="preserve">Abstract</x> On page 6594, polymer fibers are designed by P. Anikeeva and co‐workers to mimic fibrous geometry of the nerves allow simultaneous optical stimulation and neural recording in the spinal cord. The cover picture illustrates the flexibility of the bifunctional neural probes and their ability to accommodate deformation due to the movement of vertebrae. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>